From business correspondence to message exchange : the notion of genre in business communication - Louhiala-Salminen, Leena (1999)
This book completes a project which has examined the salient features of contemporary business communication, specifically from the viewpoint of technological advancements in communications media. An overview of the earlier substudies as well as in-depth accounts of both the theoretical framework of genre analysis and the notion of business communication are presented. In addition, the present book includes a report of a substudy that analyzed authentic business messages as textual products focusing on the characteristic formal elements, on the one hand, and on the metadiscoursal items found in letters, faxes, and email messages, on the other. The concepts of genre and discourse community were used throughout the project to examine written business messages and business professionals' views of their communication. The results indicate that the old-established genre of a 'business letter' has given way to a 'business fax' and a 'business email message', which shift has changed both business discourse practices and textual products. Through the membership of the specific discourse community, business professionals acquire the relevant genre knowledge which they utilize to achieve their aims. Effectiveness and efficiency are the criteria against which the 'quality' of communication is assessed, both among native and non-native language users. Although teaching is not directly investigated, various implications are discussed. The significance of a contextualized message is highlighted, as opposed to a mechanistic 'learn-this-model' approach.